Healthcare professionals’ perspectives towards the digitalisation of paediatric growth hormone therapies: expert panels in Italy and Korea - Rivera Romero, Octavio; Chae, Hyun Wook; Faienza, Maria Felicia; Vergani, Edoardo; Cheon, Chong Kun; Di Mase, Raffaella; Frasca, Francesco; Lee, Hae Sang; Giavoli, Claudia; Kim, Jihyun; Klain, Antonella; Moon, Jung Eun; et al. (Frontiers in Endocrinology, 2024)
To analyze the perspectives of healthcare professionals (HCPs) regarding the acceptance of digital health solutions for growth hormone (GH) deficiency care. This study identified factors impacting HCPs' intent to use and recommend digital solutions supporting recombinanthuman growth hormone (r-hGH) therapy in Italy and Korea with a use case of connected drug delivery system (Aluetta ® with Smartdot™) integrated in a platform for GH treatment support (the Growzen™ digital health ecosystem).Methods: Participatory workshops were conducted in Rome, Italy and Seoul, Korea, to collect the perspectives of 22 HCPs on various predefined topics. HCPs were divided into two teams, each moderated by a facilitator. The workshops progressed in five phases: introduction of the project and experts; capturing views on the current context of digitalization; perceived usefulness and ease of use of Aluetta ® with Smartdot™; exploration of the perception of health technology evolution; and combined team recommendations. Data shared by HCPs on technology acceptance were independently analysed using thematic analysis, and relevant findings were shared and validated with experts.Results: HCPs from both Italy and Korea perceived Aluetta ® with Smartdot™ and the Growzen™ based digital health ecosystem as user-friendly, intuitive, and easy-to-use solutions. These solutions can result in increased adherence, a cost-effective healthcare system, and medication self-management. Although technology adoption and readiness may vary across countries, it was agreed that using digital solutions tailored to the needs of users may help in data-driven clinical decisions and strengthen HCPpatient relationships.HCPs' perspectives on the digitalization in paediatric GH therapies suggested that digital solutions enable automatic, real-time injection data transmission to support adherence monitoring and evidence-based therapy, strengthen HCP-patient relationships, and empower patients throughout the GH treatment process.